THE EFFECT OF PELVIC ROCKING EXERCISE WITH A GYM BALL ON REDUCING LABOR PAIN INTENSITY IN THE FIRST STAGE AT TPMB TELLY KUSNAETI, CILEUNGSI, BOGOR - Kusniati, Teli; Karo, Marni BR; Wati, Puri Kresno (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2025)
Normal childbirth often induces stress and anxiety, especially in first-time mothers. To alleviate pain and facilitate fetal descent during labor, non-pharmacological methods such as pelvic rocking using a gym ball can be employed. This exercise involves moving the pelvis and waist in various directions to strengthen the abdominal, waist, and hip muscles. Using a gym ball enhances pelvic mobility and rotation while allowing exercises in sitting or upright positions, which may promote perineal relaxation and pain relief during labor. This study aimed to assess the impact of pelvic rocking exercises with a gym ball on labor pain intensity during the first stage at TPMB Tely Kusnaeti, Cileungsi, Bogor. A one-group quasi-experimental approach was utilized, involving 30 participants selected via purposive sampling. The research was conducted from August to September 2023. The hypothesis was tested using the Wilcoxon test, yielding a p-value of 0.000 (p 0.005), indicating a significant effect following the pelvic rocking exercises. Consequently, the alternative hypothesis was accepted, and the null hypothesis was rejected, confirming the significant impact of pelvic rocking with a gym ball.